The Implementation of Multicultural Islamic Religious Education in the Families of Primary School-age Children in Putrajawa, Selaawi Garut - Mukhsin, Mukhsin; Muslihudin, Muslihudin; Mutaqin, Ade Zaenul; Nasir, Muhammad (Dinamika Ilmu, 2024)
The community of Putrajawa, Selaawi Garut, is known for its cultural and religious diversity. Parents face the challenge of ensuring that Islamic religious education within the family instills not only religious understanding but also an appreciation for diversity. Exclusive religious teachings can foster intolerance, making it crucial to embed values of tolerance and inclusivity, especially in primary school-aged children. Parents play a strategic role in teaching these values through multicultural-based Islamic religious education. This study explores the implementation of multicultural Islamic religious education for primary school-aged children in Putrajawa, Selaawi Garut, focusing on the goals, materials, and methods of multicultural education in the family context. The research used a descriptive-qualitative approach, with data collected through interviews, observations, documentation, and triangulation. The results show that parents aim to raise children who are religious, respect diversity, and are tolerant. Educational materials include teaching monotheism, worship, noble morals, cultural diversity, and universal values like justice and respect. Methods include setting good examples, fostering good social relations, promoting independence, and guiding children with gentleness.